THE THE EFFECT OF ABDOMINAL STRETCHING EXERCISE ON DECREASING THE PAIN INTENSITY OF DYSMENORRHEA IN NURSING DEPARTMENT STUDENTS IN STIKES MANDALA WALUYA KENDARI: ABDOMINAL STRETCHING EXERCISE - Asri Dwi Novianti; Ida Angresti (STIKes Mandala Waluya Kendari, 2022)
Background: This study was conducted on an initial survey by interviewing ten female students who experienced dysmenorrhea. Five of them reported their pain, although they could still carry out daily activities. Fourof themsaid the pain was in the lower abdomen, radiated to the back, and needed medication to relieve pain. At least their daily activities were not disturbed.One of them said in crying because of pain and could not get up or experienced a decreased range of consciousness, so she could not carry out daily activities even though she was taking medication to reduce pain intensity. Therefore, this study aimed to determine the effect of abdominal stretching exercises on reducing the power of dysmenorrhea pain in nursing department students. Methods: The type of research used is pre-experimental with one group Pre-test Post-test design, namely analysis that uses one group of subjects. The population in this study was 289 female students, with a sampling technique using purposive sampling with 31 respondents. The analysis method uses a non-parametric statistical test, namely the Wilcoxon sign rank test, using a significant level of 0.1. Results: Based on the statistical results, the value of the Wilcoxon test for reducing the pain intensity of dysmenorrhea in female students showed 0.000. It means that the significance value is less than 0.1 so that the hypothesis in this study is accepted. This implies that abdominal stretching exercise could decrease the intensity of dysmenorrhea pain in nursing department students in Stikes Mandala Waluya Kendari. Conclusion: It is hoped that female students who experience dysmenorrhea prioritize non-pharmacological interventions to relieve pain.